2009
DOI: 10.1002/cjoc.200990295
|View full text |Cite
|
Sign up to set email alerts
|

Binding Interaction of Captopril with Metal Ions: A Fluorescence Quenching Study

Abstract: The binding interaction of captopril (CPL) bimolecular quenching constant K q , binding constant K and the binding sites "n" were determined together with their thermodynamic parameters at 27 and 37 ℃. The positive entropy change indicated the gain in configurational entropy as a result of chelation. The process of interaction was spontaneous and mainly ∆S-driven.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
(11 reference statements)
0
12
1
Order By: Relevance
“…As shown in table 2, the fluorescence intensity decreases in the order, Ni 2þ 4 Cu 2þ 4 Zn 2þ 4 Cd 2þ , in contrast with the order reported [33]. Probably, collisional quenching differences between the four complexes may be related to the structure of the complexes.…”
Section: Ir Spectracontrasting
confidence: 78%
“…As shown in table 2, the fluorescence intensity decreases in the order, Ni 2þ 4 Cu 2þ 4 Zn 2þ 4 Cd 2þ , in contrast with the order reported [33]. Probably, collisional quenching differences between the four complexes may be related to the structure of the complexes.…”
Section: Ir Spectracontrasting
confidence: 78%
“…Among these thermodynamic parameters, the negative DG value implies that the interaction process between BPP and nickel(II) ion is spontaneous [25]. The positive DH value indicates that their interaction is an endothermic process, and the positive DS value also reveals the chelating characteristic of the chemosensor BPP with nickel(II) ion [26].…”
Section: Thermodynamic Parametersmentioning
confidence: 98%
“…If the K SV decreased with increased temperatures, it could be concluded that the quenching process is not a dynamic quenching but a static quenching. [11][12][13] For dynamic quenching, the mechanism can be described by the Stern-Volmer equation:…”
Section: Fluorescence Quenching Spectra and Quenchingmentioning
confidence: 99%
“…The phase modulation method was used to obtain fluorescence lifetime. [11] The UV-vis absorption spectra were recorded with a UV-169 spectrophotometer (Elico Ltd., India). All potentiometric measurements were done with Elico-LI-120 pH meter.…”
Section: Apparatus and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation